A Detailed Study on Application of Mathematical Modeling Technology by Computer Sciences Research scholars in the selected Universities of Tamil Nadu State- Case Study Report - Raj, John William Jeba (Indian Journal of Educational Technology, 2021)
The successful innovative process in any computer sciences research is based on effective implementation of mathematical modeling techniques. Recently, the Computer sciences research organizations in India and abroad ignored the importance of mathematical modeling techniques in their research process and gave no places in their curriculum. In the present study the investigator applied random sampling on research scholars and has tried to formulate eight hypotheses connecting the innovative and implementation variables and examined the relationships between innovative and implementation variables. By using regression analysis as well as by Scaffee's Post hoc test, the result demonstrated that innovative and implementation variables are significantly related. This implies that implementation of mathematical modeling technology in the computer sciences research was not successful. The investigator tried to identify the factors that would determine the successful implementation of mathematical modeling technology in the said research field. It is critically important that mathematically trained and technologically competent research experts should be appointed and utilized as resources in the computer research policy making bodies. Research organization with mathematical modeling facility should collaborate with those that lack those that lack them to provide all research activities and an opportunity to witness, learn from successful modeling related experiments.